Arms control for the third nuclear age : between disarmament and armageddon - Cooper, David A. (Georgetown University Press, 2021)
In Arms Control for the Third Nuclear Age, David A. Cooper offers a reappraisal of classic arms control theory that advocates for reprioritizing deterrence over disarmament. In this very different era of great power rivalry, this hard-nosed approach will be a must-read for scholars, students, and practitioners of nuclear arms control.